Amphiphilic reactive poly(glycidyl methacrylate)-block-poly(dimethyl siloxane)-block-poly(glycidyl methacrylate) triblock copolymer for the controlling nanodomain morphology of epoxy thermosets. (November 2019) - Zhou, Quan; Liu, Qi; Song, Ning; Yang, Jingyi; Ni, Lizhong
Graphical abstract: When the amphiphilic poly(glycidylmethacrylate)-b-poly(dimethylsiloxane)-b-poly (glycidyl methacrylate) (PGMA-b-PDMS-b-PGMA) triblocks was introduced into epoxy matrix, epoxy-insoluble PDMS microphase could be surrounded by the miscible PGMA subchains and the separation has appeared before curing reaction because the formation of nanophase was drove by intermolecular specific interactions physically, indicating the formation mechanism of nanostructures in the epoxy containing triblock copolymer was self-assembly. With increasing the concentration of the triblock copolymer, the "core-shell" spherical particles in epoxy matrix: PDMS block is "spherical core" and PGMA is "spherical shell" were appeared and interconnected gradually. Because of the high temperature resistance and flexibility of silicon-oxygen bonds of PDMS sub-chain, the Tg and heat-resistance of DGEBA/PGMA-b-PDMS-b-PGMA toughened blends was increase, meanwhile the fracture toughness of the blends was significantly increase due to the introduction of reactive PGMA, which can form a stable covalent bond with the epoxy group been fixed by DDS after self-assembly. Highlights: Amphiphilic PGMA-b-PDMS-b-PGMA triblock copolymer with low polymer dispersity index can form a stable covalent bond with the epoxy network fixed by DDS. The morphological of DGEBA/PGMA-b-PDMS-b-PGMA blends transform snowflake nanostructure to spherical microphase. Tg value and fracture toughness as well as heat resistance of the blends were increased by incorporating the copolymer. Abstract: The amphiphilic reactive tricopolymer Poly(glycidylmethacrylate) -b-Poly(dimethylsiloxane)-b-Poly(glycidylmethacrylate) (PGMA-b-PDMS-b-PGMA) was synthesized via atom transfer radical polymerization (ATRP) from the PDMS macro-initiator and glycidylmethacrylate (GMA). The internal structure of the reactive tricopolymer was described by Fourier transform infrared spectroscopy (FITR), nuclear magnetic resonance spectroscopy (NMR) and gel permeation chromatography (GPC). The PGMA-b-PDMS-b-PGMA consisted of reactive epoxy-miscible PGMA blocks, which can been involved in the cross-linking network by covalent bonds, and an epoxy-immiscible PDMS block, which separated to give the nanostructures. The morphology of the nanostructure thermosetting blends before and after curing was not much different and as well as the difference in miscibility between its subchains, inferring the formation followed the self-assembly mechanism. Static contact angle measurement and differential scanning calorimetry (DSC) indicated that the hydrophobic and the glass transition temperature were significantly increased by introducing the reactive triblock copolymer.